Integrated Transcriptomic and Metabolomic Analyses Reveal the Mechanisms Underlying Anthocyanin Coloration and Aroma Formation in Purple Fennel - Zhang, Yanjie; Zhao, Qing; Feng, Youwei; Dong, Yuanhang; Zhang, Tianjiao; Yang, Qiu; Gu, Huihui; Huang, Jinyong; Li, Yan (Frontiers in Nutrition, 2022)
The color and aroma are significant traits of vegetables and fruits, but the metabolic and molecular mechanisms underlying anthocyanin accumulation and aroma formation remain almost unknown in fennel (Anethum foeniculum L.), which is a crucial vegetable crop and grown widely for aromatic leaves and bulbs. Here, ten major anthocyanins identified and quantified by UHPLC-Q-Orbitrap HRMS (Ultra-High Performance Liquid Chromatography coupled with quadrupole Orbitrap high-resolution mass spectrometry) were mainly responsible for the coloration of purple fennel leaf. With the application of GC-MS, metabolomics analysis found that the reduced volatile phenylpropanoids including isoeugenol, trans-isoeugenol and apiol chiefly account for the characteristic aroma changes of the purple fennel. Moreover, the characteristic anthocyanin coloration and aroma formation in purple fennel were systematically studied with the integrated transcriptomics and metabolomics. The critical genes associated with biosynthesis and regulation of anthocyanins and volatile phenylpropanoids were isolated and studied carefully in transiently transfected tobacco cells and transgenic tomato plants. Together with the results of UHPLC-Q-Orbitrap HRMS, RT-qPCR and Y2H (yeast two hybrid), it is proved that the metabolic flux redirection of phenylpropanoid pathway primarily regulated by a functional MYB-bHLH-WD40 complex consisting of AfTT8, AfMYB7, and AfTTG1 accounts for the characteristic anthocyanin coloration and aroma formation in purple fennel leaf. The systematic understanding of the anthocyanin accumulation and aroma formation will assist in the improvement of fennel resource utilization and breeding.